Macrophage Activation and Functions during Helminth Infection: Recent Advances from the Laboratory Mouse - Marion Rolot; Benjamin G. Dewals (Journal of Immunology Research)
Macrophages are highly plastic innate immune cells that adopt an important diversity of phenotypes in response to environmental cues. Helminth infections induce strong type 2 cell-mediated immune responses, characterized among other things by production of high levels of interleukin- (IL-) 4 and IL-13. Alternative activation of macrophages by IL-4 in vitro was described as an opposite phenotype of classically activated macrophages, but the in vivo reality is much more complex. Their exact activation state as well as the role of these cells and associated molecules in type 2 immune responses remains to be fully understood. We can take advantage of a variety of helminth models available, each of which have their own feature including life cycle, site of infection, or pathological mechanisms influencing macrophage biology. Here, we reviewed the recent advances from the laboratory mouse about macrophage origin, polarization, activation, and effector functions during parasitic helminth infection.